2007 IEEE International Conference on Acoustics, Speech and Signal Processing - ICASSP '07 2007
DOI: 10.1109/icassp.2007.366211
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Detecting Cropped and Recompressed Image Block

Abstract: One of the most common practices in image tampering involves cropping a patch from a source and pasting it onto a target. In this paper, we present a novel method for the detection of such tampering operations in JPEG images. The lossy JPEG compression introduces inherent blocking artifacts into the image and our method exploits such artifacts to serve as a 'watermark'for the detection of image tampering. We develop the blocking artifact characteristics matrix (BACM) and show that, for the original JPEG images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
101
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(103 citation statements)
references
References 8 publications
1
101
0
1
Order By: Relevance
“…Estimating the quantization from only the underlying DCT coefficients is both computationally nontrivial, and prone to some estimation error, which leads to vulnerabilities in the forensic analysis. In comparison to [13], our approach does not require that the image be cropped in order to detect blocking inconsistencies. In addition, our approach can detect local tampering unlike the global approach of [13] which can only detect an overall crop and re-compression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimating the quantization from only the underlying DCT coefficients is both computationally nontrivial, and prone to some estimation error, which leads to vulnerabilities in the forensic analysis. In comparison to [13], our approach does not require that the image be cropped in order to detect blocking inconsistencies. In addition, our approach can detect local tampering unlike the global approach of [13] which can only detect an overall crop and re-compression.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to [13], our approach does not require that the image be cropped in order to detect blocking inconsistencies. In addition, our approach can detect local tampering unlike the global approach of [13] which can only detect an overall crop and re-compression. And in comparison to [14], our approach, although likely not as powerful, is computationally much simpler and does not require a large database of images to train a support vector machine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the authors in [7] proposed a method to determine whether a BMP image has been JPEG compressed previously by detecting the block artifact effects. It has also been shown that JPEG image splicing [8] and MPEG recompression [9] can be exposed based on the block artifacts. In most prior literatures, it is always assumed that the image is compressed by a known scheme such as JPEG, MPEG with a fixed block size of 8 × 8 or 16 × 16.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, most existing works on block artifacts are proposed with the purposes of image restoration and enhancement, only a few are for forensics purposes [7,8,9,10]. It is well known that the block artifact is bad for the quality of the image.…”
Section: Introductionmentioning
confidence: 99%